Forensic Examination in a Homicide Case Due to Suffocation: A Case Report - Kusumaningrat, Donald Rinaldi; Yapiter, Jesslyn Alvina (Medicinus, 2025)
Background: Smothering is a form of death due to asphyxia which is caused by obstruction of air flow from the mouth and nose which can be caused by various things such as hands, air-tight paper or textiles. Homicide smothering often occurs in infants, children, vulnerable adults and individuals with limited mobility. Smothering will cause a person to die from suffocation. Case Description: The body of a 4 year 9 months old female was found smothered. On external examination, bruises resembling grips were found on both left and right upper arms, bruises resembling grips were also found on both left and right thighs. There were blackish purple bruises on the back. On internal examination, petechial bleeding was found in the heart. Discussion: Smothering is a form of asphyxia caused by obstruction of the external respiratory opening, either by hand or by other means. Apart from that, it can also be caused by blockage of the nasal and oral cavities due to the entry of foreign objects. Based on the facts obtained from the examination, injuries were found due to blunt force in the form of bruises on the upper and lower lips, back area, upper and lower arms. So it can be concluded that the victim died from suffocation due to the closure of the respiratory tract. Conclusions: External examination and autopsy of the body are very important things to do, especially in crucial cases where there is done to help seek justice for the victim.